Correlation Between Tissue Changes and Clinical Outcomes in urinary Bladder Carcinoma patients in Babylon - Alsaqi, Sabreen Saleem Abd Alkreem (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Urinary bladder cancer is among the most prevalent malignancies worldwide, with its progression strongly influenced by clinicopathological characteristics. Specific Background: Despite extensive documentation of urothelial carcinoma behavior, variations in tissue morphology and their clinical correlations remain insufficiently clarified in regional populations. Knowledge Gap: Limited data exist regarding how histopathological patterns relate to tumor grade, stage, and patient demographics in Iraqi cohorts. Aim: This study examined the key pathological alterations in 50 bladder cancer patients to determine the association between tissue characteristics, tumor aggressiveness, and clinical outcomes. Results: High-grade tumors were predominant (80%), with most cases invading the deep muscle (78%). Men were disproportionately affected, and smoking emerged as a major risk factor. A significant correlation was observed between patient age and both tumor grade and stage, indicating that older individuals tend to present with more advanced disease. Novelty: The study highlights distinct high-grade T1 variants that may offer additional prognostic value, emphasizing heterogeneity within early-stage tumors. Implications: These findings underscore the need for improved risk-stratification strategies, earlier detection, and larger prospective studies to refine diagnostic and management protocols for bladder carcinoma.|Highlight : The study shows most cases present as high-grade and advanced stage. Smoking and chemical exposure appear as major contributing risks. Tumor grade and invasion depth remain key indicators for diagnosis and management. Keywords : Bladder Cancer, Papillary Carcinomas, Histopathological Features, Tumor Grade, Age